Tingkat Kecerahan Lampu Belakang, Visibilitas, dan Kecepatan Kendaraan yang Melewati Jalan Tol Cipali Km 188-108 Arah Jakarta - Amrullah, Afif Amir (Jurnal Bisnis Indonesia, 2024)
The number of accidents on the Cipali Toll road between 2019/2021 was 1000 accidents which killedtotal of 223 people, and 170 of them are known to have died as a result of rear-end collisions. Thefactor of lack of anticipation of speed and distance from the vehicle in front is thought to be the maincause. This condition can be caused by vehicle speed exceeding the limit or the front vehicle is lessvisible, so it is necessary to check the illumination level of the rear lights. This research uses adescriptive observation method. The samples are vehicles passing through the Cipali KM between 188and 108 toll road towards Jakarta, Sunday 29 January 2023 at 19.30-21.00 WIB. The speed of theobserver vehicle was 80-100 km/hour. The standard brightness level was measured using a luxmeteron the rear lights of the 2016 Suzuki Ertiga Dreza. The research results showed that some tollroadsections had lighting. There were 316 SUVs, minibuses, buses and trucks that were passed orpass through the researcher's path. From 56 truck type vehicles, 16 Trailer truck type vehicles and 1minibus had a low level of brightness, with less visible category and speed less than standard which isthought to have contributed to rear-end collisions. The conclusion is, there are still vehicles that haverear lights with low levels of brightness, less visible and low speeds which pose a risk of rear-endcollisions. So strict supervision and regulations are needed regarding the conditions for vehiclespermitted to use Toll roads at night.Keywords: Brightness; Road Accidents; Rear-End Collisions; Rear Lamp